Effect of Estradiol and Soy Extract on the Onset of PTZ-Induced Seizure in Ovariectomized Rats: Implications for Nurses and Midwives - Afsordeh; Heydari; Salami; Sadat Alavi; Arbabi; Karimi; Hamidi (Kashan University of Medical Sciences, 2016)
Background In many epileptic women, the ovarian cycle influences the risk and severity of seizures. Previous studies have reported inconsistent findings regarding the neural excitatory effects of estrogen. Soybean is a rich source of plant estrogens. Therefore, soy intake can affect the risk and severity of seizures in women. Nurses and midwives need to be aware of the effects of diets containing estrogen in pregnant and post-menopausal women, as well as during the sexual cycle periods. Objectives Due to the limitations of human studies, this study aimed to investigate the effect of estradiol and soy extract on the onset of pentylenetetrazol (PTZ)-induced seizures in ovariectomized rats. Materials and Methods In this experimental study, sixty female Wistar rats were randomly divided into six groups of ten. All of the groups except for the negative control groups were ovariectomized. One group received estradiol (100 µg/kg), one group was treated with alcoholic extract of soy (20 mg/kg), and the other group received vehicle over 28 days. PTZ (90 mg/kg) was used to induce seizure in all groups. Behavioral changes were observed over 30 minutes. All data were analyzed using a two-way analysis of variance with Tukey's post-hoc test. Results The mean ± SD of the clonic seizure threshold was 61.84 ± 8.53 in the group that received estradiol, while it was 71.70 ± 10.85 in the control group, 64.69 ± 3.23 in rats with laparotomy without removing the ovaries, 51.30 ± 6.84 in rats with laparotomy and removing the ovaries, 52.7 ± 7.18 in ovariectomized rats that received sesame oil as vehicle, and 59.2 ± 4.91, in the soy groups. Therefore, estradiol significantly increased the clonic seizure threshold, while the alcoholic extract of soy had no effect. Conclusions We concluded that the chronic administration of estradiol has an anticonvulsant effect in the animal model. However, alcoholic extract of soy has no effect on the onset of clonic seizures.